Characteristics of band modulation FET on sub 10 nm SOI. (22nd February 2019) - Kwon, Sehyun; Navarro, Carlos; Gamiz, Francisco; Cristoloveanu, Sorin; Galy, Phileppe; Choi, Minho; Kim, Yong Tae; Ahn, Jinho
Abstract: The electrical characteristics of band modulation FET are investigated with energy band diagrams between drain to source through intrinsic gate region according to front/back gates and drain bias conditions. The drain current–voltage and transfer characteristics show extremely steep slope with minimum subthreshold swing of 1.6 mV/decade. Memory window is 0.27 V, which is determined with turn on voltages at "0" and "1" states through multiple cycles of write and read operations. Memory performance also shows that current margin to distinguish the "0" and "1" state has the maximum value of over 100  μ A at V D of 1.2 V. But, the current margin is relatively less affected by the front and back gate bias under the conditions that V D is applied in the memory window range and the current at "0" state remains low.